Conversion Narratives in Early Modern England - Shinn, Abigail. author. aut Link
XI, 255 p.
Keywords: This book is a study of English conversion narratives between 1580 and 1660. Focusing on the formal, stylistic properties of these texts, it argues that there is a direct correspondence between the spiritual and rhetorical turn. Furthermore, by focusing on a comparatively early period in the history of the conversion narrative the book charts for the first time writers’ experimentation and engagement with rhetorical theory before the genre’s relative stabilization in the 1650s. A cross confessional study analyzing work by both Protestant and Catholic writers, this book explores conversion’s relationship with reading; the links between conversion, eloquence, translation and trope; the conflation of spiritual movement with literal travel; and the use of the body as a site for spiritual knowledge and proof.